Managing Crohn’s Disease Postoperative Recurrence Beyond Prophylaxis: A Comprehensive Review with Meta-Analysis - Andrei Ovidiu Olteanu; Artsiom Klimko; Eugen Nicolae Tieranu; Andreea Daniela Bota; Carmen Monica Preda; Ioana Tieranu; Christopher Pavel; Mihai Radu Pahomeanu; Cristian Valentin Toma; Adrian Saftoiu; Elena Mirela Ionescu; Cristian George Tieranu (Biomedicines)
Background and Aims: Postoperative recurrence in Crohn’s disease remains a significant clinical challenge, with high recurrence rates despite advancements in medical therapy. This study aims to evaluate the efficacy of various treatments for managing postoperative recurrence following ileocolonic resection in Crohn’s disease. Methods: A comprehensive search of PubMed, Cochrane, and Scopus databases was performed to identify studies reporting on the therapeutic management of postoperative recurrence in Crohn’s disease. Studies encompassing patients with an endoscopic Rutgeerts score of at least I2 were included. Results: Ustekinumab showed promise, achieving significant endoscopic and clinical success in difficult-to-treat patients. Anti-TNF agents demonstrated superior endoscopic and clinical remission rates compared to mesalamine and azathioprine. Retreatment with anti-TNF therapy remained effective even after preoperative failure. Thalidomide showed efficacy in refractory Crohn’s disease, but carries significant toxicity risks, necessitating careful patient selection and monitoring. Combination therapies and non-pharmacologic strategies like enteral nutrition offer additional options, though patient compliance remains challenging. Conclusions: Personalized treatment plans based on individual risk factors and biomarkers are crucial. Infliximab is recommended as the first-line treatment, with ustekinumab and vedolizumab as alternatives in case of anti-TNF failure or intolerance. Early intervention, patient education, and ongoing evaluation are essential for optimizing long-term outcomes in managing postoperative recurrence in Crohn’s disease.